2011
DOI: 10.1002/chem.201102210
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular [2+2+2] Cycloaddition Reactions of Yne‐ene‐yne and Yne‐yne‐ene Enediynes Catalysed by RhI: Experimental and Theoretical Mechanistic Studies

Abstract: N-tosyl-linked open-chain yne-ene-yne enediynes 1 and 2 and yne-yne-ene enediynes 3 and 4 have been satisfactorily synthesised. The [2+2+2] cycloaddition process catalysed by the Wilkinson catalyst [RhCl(PPh(3))(3)] was tested with the above-mentioned substrates resulting in the production of high yields of the cycloadducts. Enediynes 1 and 2 gave standard [2+2+2] cycloaddition reactions whereas enediynes 3 and 4 suffered β-hydride elimination followed by reductive elimination of the Wilkinson catalyst to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…As it can be seen, the C−C bond to be formed in this step has a bond length of 2.008 Å. This is the highest energy barrier throughout the catalytic cycle through path A and, therefore, oxidative addition is the rds for this path, similar to some other [2+2+2] cycloadditions . Oxidative addition affords the rhodacyclopentadiene species A4 by releasing 11.0 kcal mol −1 .…”
Section: Resultsmentioning
confidence: 67%
“…As it can be seen, the C−C bond to be formed in this step has a bond length of 2.008 Å. This is the highest energy barrier throughout the catalytic cycle through path A and, therefore, oxidative addition is the rds for this path, similar to some other [2+2+2] cycloadditions . Oxidative addition affords the rhodacyclopentadiene species A4 by releasing 11.0 kcal mol −1 .…”
Section: Resultsmentioning
confidence: 67%
“…However, after some experimentation, we found that the addition of a catalytic amount of acid enhanced the selectivity with this substrate. [21] Most remarkably, the selectivities found in this study of new SIP ligands are the highest reported for substrates that cyclize through pathway II, and thus highlight the utility of ligands with PH/NH tautomerism in catalysis. Preparation of neutral Rh I complexes with SIP ligands.…”
mentioning
confidence: 53%
“…[18a] On the other hand, DFT calculations indicated that enediynes with terminal alkynes cyclize preferentially through initial alkyne-alkyne coupling (pathway II), usually leading to low enantiomeric excess. [21] Most remarkably, the selectivities found in this study of new SIP ligands are the highest reported for substrates that cyclize through pathway II, and thus highlight the utility of ligands with PH/NH tautomerism in catalysis.…”
mentioning
confidence: 53%
“…A comparative analysis can be performed at this point between linear allene–ene–allene and yne–ene–yne systems15d when submitted to a rhodium‐catalysed [2+2+2] cycloaddition reaction. Comparing the corresponding postulated mechanisms, several qualitative differences arise.…”
Section: Resultsmentioning
confidence: 99%